1988
DOI: 10.1104/pp.88.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Decarboxylation of Branched-Chain 2-Oxo Fatty Acids by Higher Plant Peroxisomes

Abstract: Peroxisomes from mung bean ( Vigna radiata L.) hypocotyls catalyze, in the presence of branched-chain 2-oxo fatty acid, CoASH and NAD, the release of C02, and the formation of NADH and acyl-CoA. The acylCoA contains one carbon atom less than the branched-chain 2-oxo fatty acid and serves as substrate for the peroxisomal acyl-CoA oxidase. CO2 release, NADH and acyl-CoA formation occur in 1:1:1 stoichiometry. For the first time the data demonstrate directly the oxidative decarboxylation of branched-chain 2-oxo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 11 publications
0
25
1
Order By: Relevance
“…during sucrose starvation (16,20) when massive production of branched-chain amino acids is triggered during the course of macroautophagy. These hypotheses require further attention, and the physiological significance of the possible dual localization of leucine degradation in plant cells (peroxisomes [10,11], mitochondria [this work]) remains to be established. Finally, it is also possible that mitochondrial MCase can be involved in the mevalonate synthesis pathway (via 3-hydroxyl-3-methylglutaryl-CoA).…”
Section: Discussionmentioning
confidence: 99%
“…during sucrose starvation (16,20) when massive production of branched-chain amino acids is triggered during the course of macroautophagy. These hypotheses require further attention, and the physiological significance of the possible dual localization of leucine degradation in plant cells (peroxisomes [10,11], mitochondria [this work]) remains to be established. Finally, it is also possible that mitochondrial MCase can be involved in the mevalonate synthesis pathway (via 3-hydroxyl-3-methylglutaryl-CoA).…”
Section: Discussionmentioning
confidence: 99%
“…Thc enzymatic reaction was initiated by the addition of CoASH. Aliquots of the reaction mixture were treated as described by Bushan et al (1986) and analyzed by HPLC, which was performed with slight modifications as described earlier (Gerbling and Gerhardt, 1988). HPLC was carried out by the use of a RP-18 Knauer column (250 X 4.6 mm).…”
Section: Coa-ester Separation On Reverse-phase Hplcmentioning
confidence: 99%
“…5). In vitro assays have demonstrated that BCAA are catabolized in isolated plant peroxisomes (9,10). However, several potential BCAA catabolic enzymes in Arabidopsis, pea, and soybean have been isolated from mitochondria or contain apparent mitochondrial transit signals (Fig.…”
Section: Functional Complementation Of Chy1 With a Human Hibyl-mentioning
confidence: 99%
“…The subcellular localization of BCAA catabolism in plants remains controversial. Although BCAA catabolism is mitochondrial in mammals, peroxisomes isolated from mung bean and sunflower cotyledons can convert labeled BCAAs to propionyl-CoA and acetyl-CoA (9,10).…”
mentioning
confidence: 99%